Pengaruh Kecerdasan Emosional Dan Komitmen Kerja Terhadap Semangat Kerja Pegawai Pada Perusahaan Daerah Air Minum Lawu Tirta Kabupaten Magetan - Sulaksono, Hari (Universitas Merdeka Madiun, 2019)
This study aimed (1) to analyze the influence of emotional intelligence on employee morale PDAM Tirta Lawu Magetan; (2) to analyze the influence of the work commitment to employee morale PDAM Tirta Lawu Magetan; and (3) to analyze the influence of emotional intelligence and commitment to work simultaneously on employee morale PDAM Tirta Lawu Magetan. Respondents in this study were employees of the Regional Water Company Lawu Tirta Magetan which amounted to 57 people. The data collection technique using questionnaires and the analysis of data using multiple linear regression analysis, an analysis of the determinants, t test and F test The findings showed that (1) there is the influence of emotional intelligence on employee morale PDAM Tirta Lawu Magetan; (2) there are significant commitment to work towards employee morale PDAM Tirta Lawu Magetan; and (3) there is the influence of emotional intelligence and commitment to work simultaneously on employee morale PDAM Tirta Lawu Magetan.